CONCEPT OF RESEARCH RELATED TO THE DEVELOPMENT OF THE MODEL AGREEMENT RELATED SECTIONS OF ROADS - and (Municipal economy of cities. Series: «Economy science», 2013)
A model is proposed agreement related road segments based on the information characteristics of the environment movement.